Time-symmetric cycles - Chris Bernhardt (International Journal of Mathematics and Mathematical Sciences)
The main result of this note is that given any two time-symmetric cycles, one can find a time-symmetric extension of one by the other. This means that given a time-symmetric cycle, both time-symmetric doubles and square roots can be found.